EVALUATION OF PERFORMANCE ON RESIN COATED LOCAL SAND - NOR AINI BT DAUD @ ABDUL RAHIM, NOR AINI (Universiti Teknologi Petronas, 2012)
The purpose of this project is to improve well treatment method which employs resin coated material. The project is experimental oriented which study the affect of percentage of resin in coating method to the compression strength, permeability and porosity. For this project we are using local sand taken from Terengganu area. Results to be achieved are the best compressive strength and good permeability and porosity. There are possibilities to use local sand as resin coated which will be very economical method and can be commercialized. This project will be the first to use local sand as resin coated sand.